Reassessing Biological Threats: Implications for Cooperative Mitigation Strategies - Galloway, Summer Elise; Petzing, Stephanie Rachel; Young, Catharine Grace (Frontiers in Public Health, 2015)
Multiple factors ranging from globalization to ecosystem disruption are presenting the global community with evolving biological threats to local, national, and global security that reach beyond the realm of traditional bioweapons threats. As a result, mitigation strategies have adapted necessarily to the increased diversity of biological threats. In general, response and preparedness strategies have largely shifted from being primarily reactive to traditional biological weapons to more proactive in nature. In this review, we briefly explore biological threats through a wider aperture, to embrace a deeper appreciation of viral pathogens, antimicrobial resistance, and agricultural pathogens, and their potential to cause civil, economic, and political devastation. In addition we discuss current mitigation strategies codified by the Global Health Security Agenda and the One Health paradigm, as well as some of the available tools to assist with their sustainable implementation.